2017
DOI: 10.1637/11537-111416-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Cell–Adapted Infectious Bronchitis ArkDPI Vaccine is Stable and Protective

Abstract: We previously demonstrated that adaptation of an embryo-attenuated infectious bronchitis virus (IBV) Arkansas (Ark) Delmarva Poultry Industry (DPI)-derived vaccine to chicken embryo kidney (CEK) cells (CEKp7) shifted the virus population towards homogeneity in spike (S) and nonstructural protein genes. Moreover, the typical Ark vaccine subpopulations emerging in chickens vaccinated with commercial Ark vaccines were not detected in chickens vaccinated with CEKp7, indicating that kidney-cell adaptation drastical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…A variant analysis of an Arkansas-type vaccine strain of AvCoV using Illumina technology showed that the spike gene reached population homogeneity, and protection against homologous challenge, i.e., the same virus type for vaccination and challenge, was observed in birds through a study of passages in chicken embryo cells (CEK) (Zegpi et al, 2017), although a restricted (n=7) passage number was used.…”
Section: Discussionmentioning
confidence: 99%
“…A variant analysis of an Arkansas-type vaccine strain of AvCoV using Illumina technology showed that the spike gene reached population homogeneity, and protection against homologous challenge, i.e., the same virus type for vaccination and challenge, was observed in birds through a study of passages in chicken embryo cells (CEK) (Zegpi et al, 2017), although a restricted (n=7) passage number was used.…”
Section: Discussionmentioning
confidence: 99%
“…Although using one of the viral subpopulations with binding affinity for chicken cells directly as a vaccine will induce a protective immune response, these subpopulations cannot be maintained through multiple passages in embryonated chicken eggs, which is required to propagate IBV vaccine. Research has been performed to homogenize the ArkDPI viral population by adapting it for growth in chicken embryo kidney cells, however this vaccine model has not yet been shown to be commercially feasible [18].…”
Section: Introductionmentioning
confidence: 99%